2016
DOI: 10.1523/jneurosci.1519-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Group II Metabotropic Glutamate Receptors Promotes LTP Induction at Schaffer Collateral-CA1 Pyramidal Cell Synapses by Priming NMDA Receptors

Abstract: It is well established that selective activation of group I metabotropic glutamate (mGlu) receptors induces LTD of synaptic transmission at Schaffer collateral-CA1 synapses. In contrast, application of 1S,3R-ACPD, a mixed agonist at group I and group II mGlu receptors, induces LTP. Using whole-cell recordings from CA1 pyramidal cells and field recordings in the hippocampal CA1 region, we investigated the specific contribution of group II mGlu receptors to synaptic plasticity at Schaffer collateral-CA1 synapses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Co-activation of mGlu5Rs with NMDARs located in this vicinity is known to strongly enhance the function of the NMDARs 24 26 . Group II mGluRs also are located perisynaptically 27 , can enhance NMDA-evoked currents 28 , 29 , and have been implicated in the induction/maintenance of LTD 30 32 . However, unlike mGlu5Rs, they do not appear to have a role during LTD induction by LFS in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Co-activation of mGlu5Rs with NMDARs located in this vicinity is known to strongly enhance the function of the NMDARs 24 26 . Group II mGluRs also are located perisynaptically 27 , can enhance NMDA-evoked currents 28 , 29 , and have been implicated in the induction/maintenance of LTD 30 32 . However, unlike mGlu5Rs, they do not appear to have a role during LTD induction by LFS in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Canonical plasticity induced by mGlu 2/3 involves a decrease in presynaptic release probability 41 45 , and recent publications have shown that activation of mGlu 2/3 can modify postsynaptic NMDAR receptor function under some circumstances 46 , 47 . However, the present data provide direct evidence that activation of mGlu 3 induces LTD by postsynaptic AMPAR internalization in PFC pyramidal cells, similar to the mechanism by which mGlu 5 -LTD occurs in the hippocampus and nucleus accumbens 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies support the notion that NMDARs can be downstream effectors of G i/o -coupled mGluRs. For example, mGluR7 can downregulate NMDARs through an actin-dependent mechanism (Gu et al, 2012), and agonists of mGluR2 and 3 can potentiate NMDARs via kinase-mediated pathways (Rosenberg et al, 2016). Unfortunately, limited studies have addressed the effects of group II and III mGluR activation on AMPARs or KARs.…”
Section: Glur Crosstalk Occurs By Various Mechanisms On Different Levelsmentioning
confidence: 99%